PENGARUH ATRIBUT KUALITAS AUDIT TERHADAP FREKUENSI DAN KETEPATAN WAKTU REVISI LABA YANG DIPREDIKSI MANAJEMEN: STUDI PADA PERUSAHAAN SEKTOR KEUANGAN BURSA EFEK INDONESIA - Rachel Adventia Pakpahan; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2026)
This study is motivated by the importance of earnings information as a basis for economic decision-making, where management earnings forecasts are often revised due to the emergence of new information. A high frequency of earnings revisions may reduce the credibility of management estimates, while delayed revisions can diminish the relevance of the information for investors. In this context, audit quality is considered an external monitoring mechanism that plays a role in improving the accuracy and timeliness of earnings revisions. However, prior studies show mixed results and are still limited to specific country contexts. Therefore, this study aims to examine the effect of audit quality attributes on the frequency and timeliness of management earnings forecast revisions in financial sector companies listed on the Indonesia Stock Exchange during the period 2020–2024.This study employs a quantitative approach with a causal research design. The sampling technique used is purposive sampling, resulting in 32 companies with a total of 160 observations. The independent variable in this study is audit quality, proxied by audit delay and audit firm size (KAP), while the dependent variables consist of the frequency of earnings revisions and the timeliness of earnings revisions. This study also includes firm size and profitability (ROE) as control variables. The data analysis techniques used are binary logistic regression to test the frequency of earnings revisions and multiple linear regression to test the timeliness of earnings revisions.The results show that audit delay and audit firm size do not have a significant effect on the frequency of earnings revisions, while profitability has a significant effect. Furthermore, audit delay has a positive effect on delays in earnings revisions, while audit firm size and firm size have a negative effect on the timeliness of earnings revisions. Simultaneously, all independent variables have a significant effect on the timeliness of earnings revisions. These findings indicate that audit quality has not fully reduced the frequency of earnings revisions but plays a role in improving the timeliness of earnings revision disclosures, thereby enhancing the usefulness of financial information for users.